Displaced within homelands : the IDPs of Bangladesh and the region - Abrar, Chowdhury Rafiqul; Lama, Mahendra P.; Refugee and Migratory Movements Research Unit. (Dhaka : Refugee and Migratory Movements Research Unit, 2003)
On forced internal migration in Bangladesh, and South Asia; contributed articles.
Includes bibliographical references and index.
Keywords: Migration, Internal -- Bangladesh; Internally displaced persons -- Bangladesh; Forced migration -- Bangladesh; Migration, Internal -- South Asia; Internally displaced persons -- South Asia; Forced migration -- South Asia